TRANSFORMASI MANAJEMEN SDM MELALUI SISTEM DATABASE TERINTEGRASI (STUDI KASUS YAYASAN PENDIDIKAN X BANDUNG) - Sari Marlia; Franciskus Antonius Alijoyo (Universitas Bina Taruna Gorontalo, 2024)
This research aims to provide insights into the role of systems in transforming the operational business processes of the foundation. In the increasingly advanced digital era, integrated database systems have become a key infrastructure in the operations of various industrial sectors, including the education sector. The X Education Foundation in Bandung utilizes a database system to transform business processes and optimize efficiency in Human Resource (HR) management. This research uses a descriptive quantitative approach with data collection methods in the form of systematically designed questionnaires using proportional purposive sampling techniques. The research results show that there has been a significant increase in terms of work time efficiency, ease of data input and processing, and the presentation of relevant information for decision-making based on objective data analysis results. This research will also provide guidelines and benefits for other Education Foundations related to the utilization of integrated database systems in better HR management.